2007
DOI: 10.1088/0268-1242/22/10/008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the InGaP window layer on the optical and electrical performance of GaAs solar cells

Abstract: A wide band gap heterolayer is usually added to the front face of GaAs and other III-V solar cells to favour transparency and to passivate the emitter. This extra front layer influences the optical behaviour of the device and therefore must be taken into account in the optimization of the antireflection (AR) coating. A set of AR layers was optimized with respect to their thicknesses for an InGaP front layer in GaAs solar cells. Complementary, numerical simulation of the whole device was performed using the D-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The measured results of both optical reflectivity and electrical performance indicated that the electrical and optical properties were not obviously influenced by a slight thickness change in the window layer. 13 Compared with solar cells A and C, the dark current of solar cell B was obviously reduced and the dark J-V curve shifted to the larger forward bias voltage. This was due to the existence of the PEC-oxidized AlGaAs layer between TiO 2 and n-AlGaAs, which passivated the AlGaAs surface and hence reduced the carrier recombination rate through the interface states.…”
Section: Resultsmentioning
confidence: 91%
“…The measured results of both optical reflectivity and electrical performance indicated that the electrical and optical properties were not obviously influenced by a slight thickness change in the window layer. 13 Compared with solar cells A and C, the dark current of solar cell B was obviously reduced and the dark J-V curve shifted to the larger forward bias voltage. This was due to the existence of the PEC-oxidized AlGaAs layer between TiO 2 and n-AlGaAs, which passivated the AlGaAs surface and hence reduced the carrier recombination rate through the interface states.…”
Section: Resultsmentioning
confidence: 91%
“…While the InGaP layer plays in some extent the role of anti-reflective coating, it is important to mention that also has a passivating role due to its high band gap with respect to Ge. A similar situation was studied for the case of a GaAs cell with InGaP window [11].…”
Section: -I-'-i-'-i-'-i-'-i-'-i-'-i-'-i-'-i-'-i-mentioning
confidence: 96%
“…The device was modeled here with a heavily doped n-type and p-type region at the front and back surface to form good ohmic contacts with the external metal contact (Belghachi and Helmaoui, 2008). A 0.025 lm thick gallium indium phosphide window layer is modeled to reduce the front surface recombination achieving a low rate of 200 cm/s (Plá et al, 2007). Individual doping concentrations and thickness of the various gallium arsenide solar cell layers were based on the device fabricated and characterized by Lee et al (2012) with the emitter, base and back surface field being 0.15 lm, 3.5 lm and 0.075 lm thick, respectively, and the corresponding dopant concentrations being 1 Â 10 18 , 2 Â 10 17 , and 4 Â 10 17 atoms/cm 3 respectively.…”
Section: Experimental -Device Modelingmentioning
confidence: 99%
“…Individual doping concentrations and thickness of the various gallium arsenide solar cell layers were based on the device fabricated and characterized by Lee et al (2012) with the emitter, base and back surface field being 0.15 lm, 3.5 lm and 0.075 lm thick, respectively, and the corresponding dopant concentrations being 1 Â 10 18 , 2 Â 10 17 , and 4 Â 10 17 atoms/cm 3 respectively. The electron and hole mobilities, conduction band and valence band density of states, and radiative recombination rate used in the simulation were obtained from Plá et al (2007). Electron affinity and dielectric permittivity were obtained from Griggs et al (2006).…”
Section: Experimental -Device Modelingmentioning
confidence: 99%